Causal Evaluation of Acute Recurrent and Chronic Pancreatitis in Children: Consensus From the INSPPIRE Group. Issue 1 (January 2017) - Gariepy, Cheryl E.; Heyman, Melvin B.; Lowe, Mark E.; Pohl, John F.; Werlin, Steven L.; Wilschanski, Michael; Barth, Bradley; Fishman, Douglas S.; Freedman, Steven D.; Giefer, Matthew J.; Gonska, Tanja; Himes, Ryan; et al.
ABSTRACT: Objectives: Acute recurrent pancreatitis (ARP) and chronic pancreatitis (CP) have been diagnosed in children at increasing rates during the past decade. As pediatric ARP and CP are still relatively rare conditions, little quality evidence is available on which to base the diagnosis and determination of etiology. The aim of the study was to review the current state of the literature regarding the etiology of these disorders and to developed a consensus among a panel of clinically active specialists caring for children with these disorders to help guide the diagnostic evaluation and identify areas most in need of future research. Methods: A systematic review of the literature was performed and scored for quality, followed by consensus statements developed and scored by each individual in the group for level of agreement and strength of the supporting data using a modified Delphi method. Scores were analyzed for the level of consensus achieved by the group. Results: The panel reached consensus on 27 statements covering the definitions of pediatric ARP and CP, evaluation for potential etiologies of these disorders, and long-term monitoring. Statements for which the group reached consensus to make no recommendation or could not reach consensus are discussed. Conclusions: This consensus helps define the minimal diagnostic evaluation and monitoring of children with ARP and CP. Even in areas in which we reached consensus, the quality of the evidence is weak, highlighting the need for further research. Improved understanding of the underlying cause will facilitate treatment development and targeting. Abstract : Supplemental Digital Content is available in the text